Research on Analysis of the EV Battery Industry in China and Situation in the Global Market - Chen, Yibo (Transactions on Economics, Business and Management Research, 2024)
This paper delves into the dynamics of the Chinese electric vehicle (EV) battery market, providing an overview of its current status, recent developments, domestic policies, and industry competitiveness. Anticipated to witness substantial growth in the future, the global electric vehicle battery industry market is a focal point of analysis. A critical examination is conducted on the challenges facing the Chinese government concerning EV battery recycling and manufacturing pollution, accompanied by recommendations for addressing these issues. Additionally, a comparative analysis is presented, spotlighting prominent Chinese companies such as CATL and BYD, which play pivotal roles as leading suppliers in the global EV battery industry. Their contributions to industry advancement and technological progress are thoroughly evaluated. Furthermore, the paper scrutinizes the current landscape of the Chinese EV battery market, focusing on two primary battery types: lithium iron phosphate and ternary lithium-ion batteries. Insights gleaned from this analysis provide valuable guidance for policymakers and industry stakeholders, informing future policy considerations and shaping the trajectory of the EV battery industry in China and beyond. By offering a comprehensive examination of the Chinese EV battery market, this study serves as a valuable resource for understanding the evolving dynamics of the industry and navigating its complexities. It underscores the importance of proactive measures to address challenges and capitalize on opportunities, ultimately driving sustainable growth and innovation in the EV battery sector.